Valuation of Time and Money - Measures for Advancing Gender Equality (MAGNET) Initiative (International Food Policy Research Institute, 2024)
The Measures for Advancing Gender Equality (MAGNET) initiative aims to broaden and deepen the measurement of women’s agency, based on the development of new tools and rigorous testing and comparison of both new and existing methods for measuring agency, and promoting the adoption of these measures at scale. By increasing the availability of innovative meaningful measures of agency for a broad range of contexts, we hope our work will lead to an improved understanding of what women’s agency is, how it manifests and how it can best be measured across contexts given the research question at hand. This tool, Valuation of Time and Money, comprises survey questions, vignettes and a simple scale to understand how men and women value additional time (including work flexibility) versus additional income, their current level of control over their time and income, and their related gender attitudes. Understanding individuals’ preferences over time and money is crucial for accurately capturing welfare and the impact of development programs. Moreover, measuring disparities in how men and women perceive and manage their time and financial resources is crucial for inclusive policymaking. This data study includes following files. 1. A survey document (including implementation guidelines). 2.Two files, CAPI_Choices and CAPI_Survey, along with the accompanying files, can be used to construct a CAPI program ready for survey implementation. Alternatively, users can use an Excel workbook "CAPI_.xlsx" that includes worksheets for survey and choices, along with others, for constructing a CAPI program ready for survey implementation.